Valorization of Andean Native Potatoes Through Chuño Processing: Effects of Potato Variety and Freezing Temperature on Physicochemical, Bioactive, Nutritional, and Technological Properties - Elmer Robert Torres-Gutiérrez; Grimaldo Wilfredo Quispe-Santivañez; Jimmy Pablo Echevarría-Victorio; David Elí Salazar-Espinoza; Joselin Paucarchuco-Soto; Henry Juan Javier-Ninahuaman; Williams Esteward Castillo-Martinez; Rebeca Salvador-Reyes (Resources)
Chuño is a traditional Andean product obtained by freezing, thawing, and drying potatoes. This study aimed to assess how different Andean potato varieties (Chihuanki Negro [C], Puka Huayro Machu [P], and Yana Huayro Machu [Y]) and freezing temperatures (−10 °C, −20 °C, and −30 °C) modulate the physicochemical (pH, acidity, and moisture), bioactive (phenolics and antioxidant activity), nutritional (proximate composition and minerals), and techno-functional (water absorption and swelling power) attributes of chuño. The results revealed that variety C retained higher macronutrient levels at 10 °C, featuring higher carbohydrates, proteins, and minerals (e.g., magnesium and zinc), while P showed enhanced fiber and mineral retention, alongside a faster rehydration and antioxidant capacity, particularly at −20 °C and −30 °C. Color differences were also noted, with P presenting reddish tones and a higher luminosity, whereas C had a more intense yellow hue linked to carotenoids. In general, −10 °C and −20 °C better preserved antioxidant compounds than −30 °C. These findings underscore how the proper selection of potato variety and freezing temperature can optimize the nutritional, functional, and sensory characteristics of chuño. However, these outcomes stem from selected samples, suggesting that further research is needed to confirm the broader applicability of the proposed method across additional varieties and process conditions.